2008
DOI: 10.5253/078.096.0108
|View full text |Cite
|
Sign up to set email alerts
|

Mating Patterns in Avian Hybrid Zones — A Meta-Analysis and Review

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…First, sexual character displacement (including reinforcement) would occur if costs associated with the reduced fitness of hybrids favored the divergence of color patterns involved in prezygotic isolation (Dobzhansky 1937; Coyne and Orr 1989, 1997; Servedio and Noor 2003). Recent evidence for a significant (mean) effect of assortative mating across 58 studies of avian hybrid zones (Randler 2008) supports a role for reproductive character displacement in the kind of rapid divergent evolution of color pattern that we have documented. Second, social character displacement may result when costs associated with misdirected intraspecific aggression favor the divergence of color patterns involved in species recognition (West‐Eberhard 1983; Kingston et al 2001; Tynkkynen et al 2005).…”
Section: Discussionsupporting
confidence: 77%
“…First, sexual character displacement (including reinforcement) would occur if costs associated with the reduced fitness of hybrids favored the divergence of color patterns involved in prezygotic isolation (Dobzhansky 1937; Coyne and Orr 1989, 1997; Servedio and Noor 2003). Recent evidence for a significant (mean) effect of assortative mating across 58 studies of avian hybrid zones (Randler 2008) supports a role for reproductive character displacement in the kind of rapid divergent evolution of color pattern that we have documented. Second, social character displacement may result when costs associated with misdirected intraspecific aggression favor the divergence of color patterns involved in species recognition (West‐Eberhard 1983; Kingston et al 2001; Tynkkynen et al 2005).…”
Section: Discussionsupporting
confidence: 77%
“…In this situation, hybridization may be encouraged when all conspecific mates are paired and the remaining unpaired individual has a choice between mating heterospecifically or not breeding. Some birds will mate heterospecifically rather than not mating at all, providing that doing so will produce viable hybrids (Randler 2002(Randler , 2008. In terms of lifetime reproductive success, hybridization with a related species may be a better alternative than remaining unpaired (Randler 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hybridisation is likely among Oenanthe species, especially between O. pleschanka and O. h. melanoleuca (Panov 2005;Aliabadian et al 2007;Randler 2008), which show a wide hybrid zone in Iran. Although there are no breeding records from O. cypriaca outside Cyprus, it may be possible that the species also breeds on the southern coast of Turkey, because the species apparently has some vagrancy potential (Förschler et al 2010) and, recently, we have suggested probable breeding of O. h. melanoleuca on Cyprus (Randler and Crabtree 2010), which may also facilitate hybridisation between the taxa.…”
Section: Playbacksmentioning
confidence: 99%
“…However, molecular studies have not been carried out to support the morphological, behavioural and bioacoustic evidence. Above and beyond the molecular analysis, prezygotic isolation-a key factor of the biological species concept-should also provide further evidence for species isolation (e.g., in assortative mating; Randler 2008). As there are no overlapping breeding areas with other Oenanthe species, hybridisation-which is common in Oenanthe species (Cramp 1988;Panov 2005;Randler 2006;Aliabadian et al 2007)-could not be assessed as a pre-requisite for the biological species concept (e.g.…”
Section: Introductionmentioning
confidence: 99%